Web Application of Knowledge Management in Broiler Production in Agriculture for Vocational Education - Wuttikorn _NJANA; Ratchadakorn Phonpakdee; Pakkapong POUNGSUK; Sirirat PETSANGSR_ (My University, 2019)
This study aimed to: 1) construct and find the efficiency of Web application of knowledge management in broiler production and 2) test and find the learning achievement after using the Web application. The research instruments in this study were: 1) an assessment form for the efficiency of the web application of knowledge management in broiler production and the web application was assessed by 7 specialists and 2) learning achievement test in the production of commercial broilers. This study used experimental research along with the pretest-posttest control group design. The subjects of this study were the students with higher vocational certificate at the Agriculture Vocation Institute. They were divided into two groups: control groups (45 persons) and experimental group (55 persons). The data obtained on the learning achievement of the two groups were analyzed using the mean and the standard deviation. Besides, the t-test (independent sample) was used to compare the difference of an average mean score. The results of the study revealed that the experimental group had a higher average mean score than the control group. In other words, there was a statistically significant difference in their average mean scores at 0.05
Keywords: Certificate; Education and Critical Thinking Development